Trade and foreign direct investments as measures of spatial integration in the Baltic Sea rim region - Andreas P. Cornett; Folke Snickars (European Regional Science Association (ERSA), 2002)
The main purpose of the current paper is to provide a closer look at the processes of economic transition and integration in the Baltic Sea Region since the early 1990s. Focal points are regional and sub-regional integrative processes with regard to trade and foreign direct investment. The crucial issue is to analyse three complementary aspects of integration of the BSR. The first is a critical assessment of the BSR as a region within the European economic system, as it has been sketched in various publications from the European Commission. Secondly the paper tries to evaluate whether the BSR constitutes a coherent functional economic region based on the analysis of economic flows within the region and to the outside. Finally, an attempt is made to identify sub-regional economic units within the BSR. Data for the paper is provided from two sources, an empirical study of trade in the Danish textile industy and a survey of foreign direct investment occurring among all countries in the Baltic Sea rim region in 2000. A special study is made of Nordic firms establishing operations in the Baltic countries.
Keywords: 330